Significado de la Maternidad y la Crianza de los Hijos, para un Grupo de Mujeres Que Ejercen el Trabajo Sexual en la Localidad de Santa Fe (2017)
The purpose of this study was to investigate the meanings of motherhood and raising a group of women who carry out sex work in the town of Santa Fe de the city of Bogotá. It was considered important to investigate sex work since it is a reality that is sometimes linked to aspects such as motherhood and raising children. children, therefore it must continue to be investigated. In relation. The theoretical model in The research supported is social constructionism, since the meanings are constructed through language in relationships with the context, in addition to history It is also part of the construction of reality. An investigation is carried out descriptive, qualitative, since it provides information about the participants and allows an approach to understanding the meanings of motherhood and parenting from the point of view of three women who carry out sex work in their own way of expression of each of them. On the other hand, the research design that was used was of a narrative type, the instrument used was the semi-structured interview, to then propose categorization of the information through the Atlas Ti software. The The main findings of this research show that the meanings of motherhood and upbringing constructed by women who carry out sex work, account for the ideal of mother who has society and the stigma of prostitution, however, this does not affect negatively, since these women have used strategies to fulfill their role as mother, being the most important and rewarding event for them.